Sensitivity analysis of spray painting process to input parameters: Validation of CFD jet impingement model against an experimental dataset. (October 2017) - Moore, Barry; Nabhani, Farhad; Askari, Vahid
Abstract: Accurate modelling of the automotive spray paint process requires using Computational Fluid Dynamic (CFD) simulations built upon a number of interacting physical models. This study examines one component of the air flow in such a simulation – impinging single jet air flow and models the results in a generalizable form to allow comparison with existing practical experiment, validating the results and allowing the development of more complex models based upon reliable results. The results in this paper compare the data produced by four variations of mesh design and wall function using the k – ε model with those produced from previous practical experimental data collected in the European Research Community on Flow (ERCOFTAC) database. The CFD data for each model shows good agreement with the experimental data set in and around the boundary layer close to the jet with particularly good results using the enhanced wall treatment and a fine resolution mesh with a y+(dimensionless wall distance) value of 1. Further refinements are required to fully resolve larger radial distances, however the general results produced show good agreement with expected phenomena.